Coffee leaf scorch caused by a strain of Xylella fastidiosa from citrus - Li, W. B.; Pria, W. D.; Teixeira, C.; Miranda, V. S.; Ayres, A. J.; Franco, C. F.; Costa, M. G.; He, C. X.; Costa, P. I.; Hartung, J. S. (Amer Phytopathological Soc, 2001)
Citrus variegated chlorosis (CVC) and coffee leaf scorch (CLS) are two economically important diseases in Brazil caused by the bacterium Xylella fastidiosa. Strains of the bacterium isolated from the two plant hosts are very closely related, and the two diseases share sharpshooter insect vectors. In order to determine if citrus strains of X. fastidiosa could infect coffee and induce CLS disease, plant inoculations were performed. Plants of coffee, Coffea arabica 'Mundo Novo', grafted on Coffea canephora var, robusta 'Apuatao 2258' were mechanically inoculated with triply cloned strains of X. fastidiosa isolated from diseased coffee and citrus. Three months postinoculation, 5 of the 10 plants inoculated with CLS-X. fastidiosa and 1 of the 10 plants inoculated with CVC-X. fastidiosa gave positive enzyme-linked immunosorbent assay (ELISA) and/or polymerase chain reaction (PCR). Eight months postinoculation, another six plants inoculated with CVC-X. fastidiosa gave positive PCR results. The two X. fastidiosa strains were isolated from the inoculated plants and showed the same characteristics as the original clones by microscopy, ELISA, and PCR. None of the plants inoculated with sterile periwinkle wilt (PW) medium as controls gave positive reactions in diagnostic tests, and none developed disease symptoms. Six months postinoculation, seven plants inoculated with CLS-X. fastidiosn and eight inoculated with CVC-X. fastidiosa began to develop characteristic CLS symptoms, including apical and marginal leaf scorch, defoliation, and reductions of internode length, leaf size, and plant height, terminal clusters of small chlorotic and deformed leaves, and lateral shoot dieback. We have demonstrated that X, fastidiosa from citrus plants is pathogenic for coffee plants. This has important consequences for the management of CLS disease and has implications for the origin of citrus variegated chlorosis disease.
Keywords: plant-pathogenic bacteria